2013
DOI: 10.3109/10582452.2013.848967
|View full text |Cite
|
Sign up to set email alerts
|

Visual Analog Scale and Pressure Pain Threshold for Delayed Onset Muscle Soreness Assessment

Abstract: Objectives: To investigate the relationship between two assessments to quantify delayed onset muscle soreness [DOMS]: visual analog scale [VAS], and pressure pain threshold [PPT].Methods: Thirty one healthy young men [25.8 ± 5.5 years] performed 10 sets of six maximal eccentric contractions of the elbow flexors with their non-dominant arm. Before and one to four days after the exercise, muscle pain perceived upon palpation of the biceps brachii at three sites [5, 9, and 13 cm above the elbow crease] was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 25 publications
(35 reference statements)
2
44
0
1
Order By: Relevance
“…subjectively during exercise exertion. 16,32 The changes in MVIC, ROM, and serum CK activity after eccentric exercise in our study were similar to those reported in previous studies 22,33 and indicate that muscle damage was induced by the exercise. The time course of the changes in VAS score and PPT was also similar to those reported after eccentric elbow-flexor exercise in previous research.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…subjectively during exercise exertion. 16,32 The changes in MVIC, ROM, and serum CK activity after eccentric exercise in our study were similar to those reported in previous studies 22,33 and indicate that muscle damage was induced by the exercise. The time course of the changes in VAS score and PPT was also similar to those reported after eccentric elbow-flexor exercise in previous research.…”
Section: Discussionsupporting
confidence: 81%
“…The time course of the changes in VAS score and PPT was also similar to those reported after eccentric elbow-flexor exercise in previous research. 22,28 As shown in Figure 2, no differences among the 3 sites (3, 9, and 15 cm above the elbow crease) were evident for the changes in the VAS and CR-10 scale values upon palpation or the PPT. A previous study 22 also showed no difference in VAS changes after elbow-flexor eccentric exercise among the 3 sites (ie, 5, 9, and 13 cm above the elbow crease).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations